Dissimilar joining of Carbon/Carbon composites to Ti6Al4V and copper by reactive resistance spot welding - Shokati, Ali Akbar (University of Waterloo, 2017)
This study aims to develop an innovative and user-friendly method for dissimilar joining of the carbon/carbon (C/C) composites to Ti6Al4V and copper through reactive resistance spot welding to form the hybrid structures. The C/C composites used in this study were a 2D C/C composite with high porosity (low strength) and a 3D C/C composite with low porosity content (high strength). It was found that the infiltration of Ti into the C/C composite and formation of a continuous thin TiC layer at the interface of the joints are the dominant mechanisms of the joining. The 2D C/C composite with the flat surface was successfully joined to Ti6Al4V due to the infiltration of the melted Ti6Al4V into the porosity of the 2D C/C composite. On the other hand, it was required to drill the rectangular grooves on the surface of the 3D C/C composite to facilitate the infiltration of the melted Ti into the 3D C/C composite and consequently obtain high strength joints. The strength of 2D C/C composite-Ti6Al4V joints was 7 MPa due to failure of the joints within the low strength 2D C/C composite. By contrast, the maximum strength of the joints using the groove-patterned high-strength 3D C/C composite was 46.14 ± 3.92 MPa. In the case of joining between the 2D C/C composite and copper, the Ti thin sheet and Ti powder interlayers were used. Regarding the joints with the Ti sheet interlayer, some defects and cracks were formed at the interface of the joints, which decreased the strength of the joints, whereas in the case of using the Ti powder interlayer, defect-free joints were obtained.